Mind Map Sebagai Metode Pembelajaran Yang Inovatif - Suryanti Galuh Pravitasari (Jurnal Ilmiah SINUS, 2014)
Every learning and teaching process is aimed at gaining the mastery and understanding of the given material in the class. In order to reach that goal, it is necessary to apply a certain method or teaching technique that is good and fun even effective so that the students can understand the material faster and better. This study is a descriptive study in which the material is gained through library research including the result of the previous researches. Using Mind Map as a method in teaching English is proved to be very  effective in making the students understand the material much easier and better. Keywords: Mind Map, teaching and learning process, Innovative